Preocupação com a forma do corpo de graduandos de Farmácia-Bioquímica - Martins, Bianca Gonzalez; Silva, Wanderson Roberto; Campos, Juliana Alvares Duarte Bonini (Instituto de Psiquiatria da Universidade Federal do Rio de Janeiro, 2015)
Objective: To determine the body shape concern among pharmacy-biochemistry students and its association with several social and labor variables and nutritional status. Methods: A total of 346 students (80.3% female) with mean age 20.2 (SD = 2.4) years were asked to answer the Body Shape Questionnaire (BSQ). The factorial and convergent validities and the internal consistencies (α) of the BSQ were calculated. The goodness-of-fit indices, the chi-square by degree of freedom ratio (c2 /df), the comparative fit index (CFI), the normed fit index (NFI), and the root mean square error of approximation (RMSEA) were also used for data analysis. The mean score of body shape concern was estimated using an algorithm generated from the confirmatory factor analysis. Analysis of variance (ANOVA) was used to compare the mean scores with variables of interest. Results: The BSQ presented adequate validity (c2 /df = 3.29; CFI = .87, NFI = .82, RMSEA = .08), and reliability (α = .97) after fit. Female students showed more body shape concern than male students (p < .001). Furthermore, the students who rated the course as dissatisfactory relative to their initial expectation (p = .048), consumed drugs under academic pressure (p < .001), thought about quitting the course (p = .002), and were overweight/obese (p < .001) also presented greater body shape concern. Conclusion: The variables gender, dissatisfaction with the course, drug intake due to academic pressure, desire of quitting the course, and the nutritional status were significantly associated with the body shape concern among the participating students.

Objetivo: Identificar a preocupação com a forma do corpo de estudantes de Farmácia-Bioquímica e sua relação com variáveis sociais e laborais e com o estado nutricional. Métodos: Participaram 346 discentes com média de idade de 20,2 (DP = 2,4) anos, sendo 278 (80,3%) do sexo feminino. Utilizou-se o Body Shape Questionnaire (BSQ). As validades fatorial e convergente e a consistência interna (α) do BSQ foram estimadas. Utilizaram-se como índices de ajustamento o qui-quadrado pelos graus de liberdade (c2 /gl), o Comparative Fit Index (CFI), o Normed Fit Index (NFI) e o Root Mean Square Error of Approximation (RMSEA). O escore médio de preocupação com a forma do corpo foi obtido por meio de algoritmo gerado na análise fatorial confirmatória. Para comparar os escores médios segundo as variáveis de interesse, utilizou-se Análise de Variância (ANOVA). Resultados: O BSQ apresentou, para a amostra de estudo, adequada validade (c2 /gl = 3,29; CFI = 0,87, NFI = 0,82, RMSEA = 0,08) e confiabilidade (α = 0,97) após ajustamento. Verificou-se que as mulheres (p < 0,001) apresentaram maior preocupação com a forma do corpo que os homens. Além disso, os estudantes que avaliaram o curso como pior que as expectativas iniciais (p = 0,048), que consomem medicamentos por causa dos estudos (p < 0,001), que já pensaram em desistir do curso (p = 0,002) e foram classificados com sobrepeso/obesidade (p < 0,001) também apresentaram alta preocupação com a forma do corpo. Conclusão: As varáveis sexo, avaliação em relação ao curso, ingestão de medicamentos por causa dos estudos, pensamento em desistir do curso e o estado nutricional apresentaram relação significativa com a preocupação com a forma do corpo entre os estudantes.
Body shape concern of the graduate students of Pharmacy-Biochemistry
Keywords: Body image; Pharmacy students; Questionnaires; Imagem corporal; Estudantes de farmácia; Questionários